2021
DOI: 10.1007/s00335-021-09869-1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative exon splicing and differential expression in pancreatic islets reveals candidate genes and pathways implicated in early diabetes development

Abstract: Type 2 diabetes (T2D) has a strong genetic component. Most of the gene variants driving the pathogenesis of T2D seem to target pancreatic β-cell function. To identify novel gene variants acting at early stage of the disease, we analyzed whole transcriptome data to identify differential expression (DE) and alternative exon splicing (AS) transcripts in pancreatic islets collected from two metabolically diverse mouse strains at 6 weeks of age after three weeks of high-fat-diet intervention. Our analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Unlike the traditional method of only reserving the longest transcript sequence for each gene identified through blastP, in this study, we chose the differential splicing CPR5 sequences for the following analysis. The differential splicing alterations had been proved to produce numerous protein structures and function variances from one gene ( Reddy, 2007 ; Park et al, 2013 ; Rehman et al, 2021 ). In the current study, we had identified multiple protein isoforms from one or two CPR5 genes in some Gossypium species, GhirCPR5.2/GhirCPR5.3,GbarCPR5.1/GbarCPR5.2/GbarCPR5.3, GmusCPR5.2/GmusCPR5.3, GdarCPR5.2/GdarCPR5.3, GlonCPR5.1/GlonCPR5.2 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the traditional method of only reserving the longest transcript sequence for each gene identified through blastP, in this study, we chose the differential splicing CPR5 sequences for the following analysis. The differential splicing alterations had been proved to produce numerous protein structures and function variances from one gene ( Reddy, 2007 ; Park et al, 2013 ; Rehman et al, 2021 ). In the current study, we had identified multiple protein isoforms from one or two CPR5 genes in some Gossypium species, GhirCPR5.2/GhirCPR5.3,GbarCPR5.1/GbarCPR5.2/GbarCPR5.3, GmusCPR5.2/GmusCPR5.3, GdarCPR5.2/GdarCPR5.3, GlonCPR5.1/GlonCPR5.2 .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function and remote cardioprotection to influence IS after I/R was evaluated in NZO and Bl6 mice, in addition to cardiovascular characterization. As a polygenic mouse model, NZO mice are an established and well-known model resembling characteristic features of T2DM disease in humans: obesity, insulin resistance, severe hyperglycemia and disturbed glucose tolerance [17][18][19][20] . As the prevalence of these conditions is about 60 %, each mouse was tested for manifest T2DM before the further examination.…”
Section: Methodsmentioning
confidence: 99%
“…Aberrantly spliced genes were identified to associate with diabetes 11 13 . It has been reported that the shorter human insulin receptor isoform can prevent downstream insulin signaling, which impairs β-cell survival 14 .…”
Section: Introductionmentioning
confidence: 99%